Strategi Penatalaksanaan Stomatitis Aftosa Rekuren pada Anemia Defisiensi Besi (Laporan Kasus) - Ahmad Ronal; Siti Aliyah (Lembaga Penelitian Universitas YARSI, 2017)
Recurrent aphthous stomatitis (RAS) is a type of lesion of the oral mucous consisting of sudden acute, painful, being recurrent, non-infectious, non- vesicular, and immunologically mediated. Chronic iron deficiency will result in iron deficiency anemia which is one of RAS predisposing factors. To ilustrate the complexity of RAS in iron deficiency anemia following the treatment strategies. Case Report: Outpatient woman, thirty years old, not married yet; came with painful aphthous on her tongue causing stiff tongue sensation and difficult to speak. She has frequent aphthous since last two months. Case Management: Diagnosis of RAS was derived from history and clinical presentation whereas iron deficiency anemia condition was derived from hematology examination. Patient has been instructed to increase iron source diet and limit tea consumption. Chlorhexidine gluconate and bee propolis were used as RAS medication. Ferro gluconate, ferrazone, and ascorbic acid were delivered as iron deficiency therapy. RAS treatment in iron deficiency anemia has to be considered both of RAS and iron deficiency condition related to their correlation.